2012
DOI: 10.1002/etc.1768
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aquatic wastewater pollution in a highly industrialized zone with sediment linear alkylbenzenes

Abstract: Abstract-Forty-five sediment samples collected from Dongjiang River, which drains one of the most industrialized and urbanized regions in South China, were analyzed for 19 linear alkylbenzene (LAB) components. The sample dry weight-based concentrations of total LABs (SLAB) ranged from 1.5 to 410 ng/g. Comparison of the relative abundances of n-dodecylbenzenes (or C 12 -LABs) and internal to external ratio (I/E) values in riverine sediment, wastewater, and sediment samples from the outfalls of paper mills, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Thus, this ratio has been proposed [34] and applied [34][35][36] as an indicator of the extent of LAB degradation. Sedimentary I/E ratios in the present study were 0.54-1.21, similar to those in shampoo (0.5-1.6) [11], and in wastewater (0.8-1.4) [37]. This possibly suggests that poorly treated municipal wastewater has been discharged into both the PRD and the eastern and western coastal areas.…”
Section: Assessment Of Sewage Pollutionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, this ratio has been proposed [34] and applied [34][35][36] as an indicator of the extent of LAB degradation. Sedimentary I/E ratios in the present study were 0.54-1.21, similar to those in shampoo (0.5-1.6) [11], and in wastewater (0.8-1.4) [37]. This possibly suggests that poorly treated municipal wastewater has been discharged into both the PRD and the eastern and western coastal areas.…”
Section: Assessment Of Sewage Pollutionsupporting
confidence: 79%
“…This possibly suggests that poorly treated municipal wastewater has been discharged into both the PRD and the eastern and western coastal areas. The sediment I/E ratios in the eastern and western coastal areas were slightly lower than those in the PRE (0.6-1.5) [15], which might suggest relatively greater discharge of untreated wastewater in eastern and western coastal areas than in the PRD regions [37].…”
Section: Assessment Of Sewage Pollutionmentioning
confidence: 76%
“…However, they were substantially lower than those in sewage sludge (Takada et al, 1994;Luo et al, 2008), suspended particles in river water from the PRD , Sumidagawa River and Tamagawa River (Takada and Ishiwatari, 1987), as well as sediments from Dongguan , Zhujiang River (Luo et al, 2008), Dongjiang River (Luo et al, 2008), Arakawa River (Takada et al, 1992), Sumidagawa River and Tamagawa River (Takada and Ishiwatari, 1987), Chaohu Lake , the coastal zones of Guangdong Province (Liu et al, 2013a), Victoria Harbor (Hong et al, 1995), Tokyo Bay (Takada et al, 1992), Jakarta Bay (Rinawati et al, 2012), Santa Monica Bay (Venkatesan et al, 2010), and South and Southern Asia (Isobe et al, 2004). The greater RLAB concentrations in the sediments of the Pearl River Delta (PRD; 1.5-2330 ng/g) and Chaohu Lake (19-5720 ng/g) were attributed to direct discharge of untreated or partially treated domestic wastewater and proximity to input sources (Luo et al, 2008;Wang et al, 2012;Zhang et al, 2012). However, lower levels of RLAB in the present study may implicate light sewage contamination in the continental shelf of China, likely due to the long distance between the sampling sites and terrestrial input sources and the strong hydrophobicity of LABs leading to their preferable deposition in nearshore areas .…”
Section: Occurrence and Spatial Distributionmentioning
confidence: 99%
“…Linear alkylbenzenes (LABs) have been utilized as markers of domestic waste, as they are raw materials in manufacture of linear alkylbenzene sulfonates, a widely used anionic surfactant (Eganhouse et al, 1983), and may be disposed to the environment as residues (1-3%) of commercial detergents (Eganhouse et al, 1983;Chalaux et al, 1995;Zeng et al, 1997). In fact, LABs have been ubiquitously detected in various environmental matrices, such as sediment (Eganhouse et al, 1983;Ishiwatari et al, 1983;Zhang et al, 2012;Liu et al, 2013a), municipal wastewater effluent (Eganhouse et al, 1983;Peterman and Delfino, 1990), river runoff (Takada and Ishiwatari, 1987;Ni et al, 2008), and biota (Murray et al, 1991;Phillips et al, 2001;Tsutsumi et al, 2002). Besides, LABs were suggested to be toxic (Gledhill et al, 1991;Johnson et al, 2007), where the acute toxicity of LABs to Caenorhabditis elegans in soil was reported as a lethal concentration of 1550 ng/g to cause 1% fatality in 24 h, with the 95% confidence limits in the range of 80-3360 ng/g (Johnson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation